Friendship as paradigm of sociality - Padiglione, Vincenzo (Quaderni di Psicologia Clinica, 2023)
In the post-modern era the social bond is weaker and we have given up the idea of progress. The reciprocity that we attributed to primary institutions and to societies founded on kinship, now is closer. By discouraging social alarm, the reciprocity is becoming the basic ingredient of human life. We no longer look for it in macrosystems and universal rules, but in everyday life and in specific realities, equipped with their systems of cooperation. This article proposes a specific thesis about it, in which cultural dynamics are anchored, even if with prudence, to the historical and relational dynamics, and the sources of reciprocity are traced both in kinship and friendship. Friendship is proposed as a personal and chosen relationship, maintained voluntarily by subjects who consider themselves distinct and equal and who establish a symmetrical reciprocity between them, characterized by an idealized declaration of no instrumentality. It is proposed that this relational paradigm has been the ideal reference for Western institutions and for the subjectivities they developed, standardizing with its characteristics the structure of societies and the forms of knowledge. Sociality as an end in itself proposed by the paradigm of friendship, far from being a factor of inhibition to social action, is instead an effective enhancement. In fact, friendship needs to be expressed in actions of mutual and manifest benevolence.
Keywords: friendship; kinship; reciprocity; post-modernity; subjectivity